Subtract (Rename Difference) Find the difference. Write In simplest form. \( 5 \frac{4}{6}-4 \frac{2}{6} \) \( 1 \frac{5}{6} \) \( 1 \frac{1}{3} \) \( 1 \frac{1}{2} \) \( 1 \frac{2}{3} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To find the difference \( 5 \frac{4}{6} - 4 \frac{2}{6} \), we first convert the mixed numbers into improper fractions. 1. Convert \( 5 \frac{4}{6} \): \( 5 \times 6 + 4 = 30 + 4 = 34 \) So, it becomes \( \frac{34}{6} \). 2. Convert \( 4 \frac{2}{6} \): \( 4 \times 6 + 2 = 24 + 2 = 26 \) So, it becomes \( \frac{26}{6} \). Now, we subtract: \( \frac{34}{6} - \frac{26}{6} = \frac{34 - 26}{6} = \frac{8}{6} \). Next, we simplify \( \frac{8}{6} \) to \( \frac{4}{3} \), which can be written as \( 1 \frac{1}{3} \). Thus, the answer is \( 1 \frac{1}{3} \).